(untitled) (International Journal of Food and Nutritional Sciences, 2020)
Quantum computing is a rapidly-emerging technology that harnesses the laws of quantum mechanics to solve the problems too complex for classical computers in era quantum computing. Quantum computing represents a paradigm shift in information processing, leveraging the principles of quantum mechanics to enable exponential gains in computational power. Quantum computing has the ability to process quickly to arrive at a solution and offers well and more computing power to the world of Artificial Intelligence systems and efficient Machine learning systems by solving small and large problems much faster. This research paper provides an overview of the principles, applications, and future prospects of quantum computing